WHO Global Strategy in Eradication of Cervical Cancer - Patiyus Agustiansyah; Rizal Sanif; Siti Nurmaini; Irfannuddin; Legiran (HM Publisher, 2021)
WHO has created a global strategy to accelerate the elimination of cervical canceras a public health problem and a world burden. Cervical cancer is a disease thatcan be prevented and cured, as long as it is detected early and treated effectively.Cervical cancer is also a disease that reflects global injustice. The burden isgreatest in low- and middle-income countries, where access to public healthservices is limited and screening and treatment for the disease has not been widelyapplied. In 2018, nearly 90% of all deaths worldwide occurred in low and middleincome countries. Furthermore, the proportion of women with cervical cancer whodie from the disease is more than 60% in these countries, more than double thenumber in many high-income countries, which is only 30%.